Dziecko-manipulant w relacji z rodzicami - Tatyana Kuzmishina (Problemy Wczesnej Edukacji)
This paper describes the manipulative behaviour of children in their relationships with parents in situations of parental demands and prohibitions. The results of research into the frequency and types of manipulation used by school children are also described.